2023
DOI: 10.3390/ijms241914868
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Spike Protein S1 Induces Methylglyoxal-Derived Hydroimidazolone/Receptor for Advanced Glycation End Products (MG-H1/RAGE) Activation to Promote Inflammation in Human Bronchial BEAS-2B Cells

Dominga Manfredelli,
Marilena Pariano,
Claudio Costantini
et al.

Abstract: The pathogenesis of coronavirus disease 2019 (COVID-19) is associated with a hyperinflammatory response. The mechanisms of SARS-CoV-2-induced inflammation are scantly known. Methylglyoxal (MG) is a glycolysis-derived byproduct endowed with a potent glycating action, leading to the formation of advanced glycation end products (AGEs), the main one being MG-H1. MG-H1 exerts strong pro-inflammatory effects, frequently mediated by the receptor for AGEs (RAGE). Here, we investigated the involvement of the MG-H1/RAGE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 41 publications
1
5
1
Order By: Relevance
“…Also, lung autopsy samples from patients with fatal COVID-19 showed alveolar-capillary barrier dysfunction, injury to alveolar and basal epithelial cells and defective tissue repair processes [ 52 ]. We observed that S1 or S2 had no effect on BEAS-2B and A549 cells viability, which is in agreement with data from Manfredelli et al [ 18 ]. In contrast to the poly (I:C) model, miR-149-5p expression was not affected by S1 or S2 transfection in BEAS-2B or A549 cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, lung autopsy samples from patients with fatal COVID-19 showed alveolar-capillary barrier dysfunction, injury to alveolar and basal epithelial cells and defective tissue repair processes [ 52 ]. We observed that S1 or S2 had no effect on BEAS-2B and A549 cells viability, which is in agreement with data from Manfredelli et al [ 18 ]. In contrast to the poly (I:C) model, miR-149-5p expression was not affected by S1 or S2 transfection in BEAS-2B or A549 cells.…”
Section: Discussionsupporting
confidence: 93%
“…TLR3 further recruits tumour necrosis factor receptor (TNFR)-associated factor-6 (TRAF6) and receptor-interacting protein to activate nuclear factor kappa B (NF-κB), which regulates the production of inflammatory cytokines [ 13 ]. There are different receptors and pathways responsible for the pro-inflammatory responses of epithelial cells to SARS-CoV-2 [ 5 , 15 , 16 , 17 , 18 ]. The SARS-CoV-2 spike protein S1 subunit possesses PAMP-like properties [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle-related diseases (LSRDs), including diabetes mellitus (DM), cardiovascular disease (CVD), and nonalcoholic steatohepatitis (NASH), are a global crisis, mostly in developing countries [ 1 , 2 , 3 , 4 , 5 ]. This is attributed to people consuming excess saccharides (e.g., glucose and fructose), proteins, and lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ancient Chinese medicine considered the concept of DM symptoms [ 7 , 8 ]. Advanced glycation end products (AGEs), which are generated from saccharides/their metabolites or derivatives and proteins, are associated with LSRDs [ 1 , 2 , 3 , 4 , 5 , 9 ]. Although AGEs have been investigated since the early 20th century, when the Maillard reaction was proven [ 9 ], their relationship with human health dates back to ancient times.…”
Section: Introductionmentioning
confidence: 99%